Neolibs, Neocons and Gender Justice: Lessons from Global Negotiations - Gita Sen (United Nations Research Institute for Social Development (UNRISD), 2005)
This paper is a reflection on the environment within which the struggle for gender justice is currently under way in the global arena. It also steps back to provide an analytical frame to explain the core of the tensions between gender justice and other elements of social/economic justice, and the strategic implications of the multiple sites in which gender relations operate. It draws from the experiences of feminists who engaged in analysis and advocacy while participating in the negotiations of the United Nations conferences of the 1990s. These conferences - on environment, human rights, population, social development, women, habitat, children, HIV/AIDS, small island states, food security, racism - and their five- and ten-year reviews have provided a unique opportunity for negotiating a progressive social agenda in a systematic and ongoing way. But even as such an agenda was being spelled out, the global economic policy terrain was almost entirely subordinated to neoliberal economic thinking dominated by the Washington Consensus. The interplay between these two sets of forces is our subject matter. The paper also comments on the implications for gender justice of the shift to a unipolar world order, and in particular, the movement from the neoliberal era to the neoconservative one. The work of feminist and other scholars and activists following the conferences of the 1990s showed clearly that security of livelihoods and an enabling economic environment are an important basis for moving forward to meet reproductive and sexual health needs through well-functioning health systems (Petchesky 2003). Yet, some of the very countries that were most vocal in their support for sexual and reproductive rights were also the most hard-nosed in South-North economic negotiations. These tensions came to the fore not only in the UN conferences themselves, especially Cairo and Beijing, but also in their 'plus five' reviews. Despite this, considerable advances were possible on reproductive and sexual health and rights during the 1990s because of the limited control over state power by religious fundamentalists. This scenario has undergone a major change in the neoconservative period with much stronger control over key levers of state power by religious fundamentalists on the one hand, and the rise of neoconservative political economy on the other. The first decade of this century has seen significant and tangible evidence of this in key conferences on HIV/Aids, Children, and Population, as well as in many other sites. This paper builds on previous analysis of the earlier phase to draw out implications for the current terrain in which feminists and allies are struggling to maintain hard-won gains and move forward.
Keywords: 330